Diagnostic Accuracy of Next Generation Sequencing Panel using Circulating Tumor DNA in Patients with Advanced Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Mariana M. Sebastião; Rodrigo S. Ho; João Paulo V. de Carvalho; Micha Nussbaum (Journal of Health Economics and Outcomes Research)
**Background/Objectives:** Until now, no meta-analysis has been published to evaluate the diagnostic performance of next-generation sequencing (NGS) panel using circulating tumor (ctDNA) in patients with advanced non-small cell lung cancer (aNSCLC). The aim of the study was to carry out a systematic review and a meta-analysis in order to determine the accuracy of NGS of ctDNA to detect six oncogenic driver alterations: epidermal growth factor receptor (EGFR); anaplastic lymphoma kinase (ALK); ROS proto-oncogene 1, receptor tyrosine kinase (ROS-1); serine/threonine-protein kinase B-RAF (BRAF); RET proto-oncogene (RET); and MET proto-oncogene, receptor tyrosine kinase (MET) exon 14 in patients with aNSCLC.